The cohomology of superspace, pure spinors and invariant integrals - Berkovits, N. [UNESP]; Howe, P. S. (Int School Advanced Studies, 2008)
The superform construction of supersymmetric invariants, which consists of integrating the top component of a closed superform over spacetime, is reviewed. The cohomological methods necessary for the analysis of closed superforms are discussed and some further theoretical developments presented. The method is applied to higher-order corrections in heterotic string theory up to alpha'(3). Some partial results on N = 2, d = 10 and N = 1, d = 11 are also given.
Keywords: extended supersymmetry; superstrings and heterotic strings; superspaces; supergravity models